Tradisi Galungan Di Desa Nglewan Kecamatan Sambit Kabupaten Ponorogo (Kajian Folklor Setengah Lisan) - Wafi, Rifqi Hibatul; Susilo, Yohan (Universitas Negeri Surabaya, 2023)
ABSTRACT The Galungan tradition in Nglewan Village is a semi-oral folklore that is still believed by the residents. The Galungan tradition has been carried out as a form of custom that has been carried out since ancient times until now. This tradition is carried out as a form of kenduri aimed at Gamelan. Galungan tradition is held twice a year by Nglewan Village community members, precisely on Wednesday Kliwon night Thursday Legi in Wuku Galungan. The purpose of this research is to find out (1) the origin of the Galungan Tradition, (2) the Galungan Tradition procession, and (3) efforts to preserve the Galungan Tradition. This research uses the theory of semi-oral folklor according to Danandjaja. The research design uses descriptive qualitative research methods. Techniques for collecting data are observation, interviews and documentation. Data validity in this research uses data source triangulation techniques and method triangulation. Data analysis techniques using data transcripts, data verification, data identification and codification, and data interpretation. The results of the research on the Galungan Tradition procession are deliberations, cleaning the place and Gamelan, preparing ubarampe, notifying invitations, wilujengan, prayers, Gamelan jamasan, and uyon-uyon adiluhung. While in the effort to preserve this Galungan Tradition there are various kinds of efforts, namely, efforts from the Government, efforts from the Community, and efforts from the School. Keywords: Half Oral Folklor, Tradition, Wuku Galungan, Gamelan ABSTRAK Tradisi Galungan di Desa Nglewan termasuk folklor setengah lisan yang masih dipercayai oleh para warga. Tradisi Galungan telah berjalan sebagai wujud kebiasaan yang sudah dilaksanakan sejak zaman dahulu hingga zaman sekarang. Tradisi ini dijalankan sebagai wujud kenduri yang ditujukan untuk Gamelan. Tradisi Galungan dilaksanakan warga masyarakat Desa Nglewan satu tahun dua kali, tepatnya dihari Rabu Kliwon malam Kamis Legi didalam Wuku Galungan. Tujuan dalam penelitian ini untuk mengetahui (1) awal mula Tradisi Galungan, (2) prosesi Tradisi Galungan, dan (3) upaya pelestarian Tradisi Galungan. Penelitian ini menggunakan teori folklor setengah lisan menurut Danandjaja. Rancangan penelitian dengan menggunakan metode penelitian deskriptif kualitatif. Teknik untuk mengumpulkan data yaitu observasi, wawancara dan dokumentasi. Keabsahan data pada penelitian ini menggunakan teknik triangulasi sumber data dan triangulasi metode. Teknik analisis data dengan menggunakan cara transkrip data, verifikasi data, identifikasi dan kodifikasi data, serta penafsiran data. Hasil penelitian pada prosesi Tradisi Galungan yaitu musyawarah, membersihkan tempat dan Gamelan, menyiapkan ubarampe, memberitahu undangan, wilujengan, doa, jamasan Gamelan, dan uyon-uyon adiluhung. Sedangkan dalam upaya pelestarian Tradisi Galungan ini ada berbagai macam upaya yaitu, upaya dari Pemerintah, upaya dari Masyarakat, dan upaya dari Sekolah. Kata Kunci: Folklor Setengah Lisan, Tradisi, Wuku Galungan, Gamelan